Urological and Medical Evaluation of Men with Erectile Dysfunction - Carson, Culley C (MedReviews, LLC, 2002)
As the medical understanding of erectile dysfunction has evolved, the approach to its evaluation must also change. A good doctor/patient rapport is crucial to making patients more comfortable talking about their sexual function. Questionnaires help elicit specific information on which to base the diagnosis and find the etiology, along with examination of the genitals and hormone and other assays. If oral therapy is unsuccessful, other studies may find underlying conditions, leading to appropriate treatment.